Data communications & computer networks : a business user's approach - White, Curt M. (CENGAGE Learning, 2016)
Providing essential information for business managers, computer programmers, system designers, as well as home computer users, this book provides a thorough introduction that includes coverage of the language of computer networks as well as the effects of data communications on business and society.